Start now: a cognitive behavioral skills training for adolescent girls with conduct or oppositional defiant disorder - a randomized clinical trial - Stadler, Christina; Freitag, Christine M.; Popma, Arne; Nauta-Jansen, Lucres; Konrad, Kerstin; Unternaehrer, Eva; Ackermann, Katharina; Bernhard, Anka; Martinelli, Anne; Oldenhof, Helena; Gundlach, Malou; Kohls, Gregor; et al. (The journal of child psychology and psychiatry, 2023)
Background Conduct disorder (CD) and oppositional defiant disorder (ODD) both convey a high risk for maladjustment later in life and are understudied in girls. Here, we aimed at confirming the efficacy of START NOW, a cognitive-behavioral, dialectical behavior therapy-oriented skills training program aiming to enhance emotion regulation skills, interpersonal and psychosocial adjustment, adapted for female adolescents with CD or ODD. Methods A total of 127 girls were included in this prospective, cluster randomized, multi-center, parallel group, quasi-randomized, controlled phase III trial, which tested the efficacy of START NOW (n = 72) compared with standard care (treatment as usual, TAU, n = 55). All female adolescents had a clinical diagnosis of CD or ODD, were 15.6 (±1.5) years on average (range: 12-20 years), and were institutionalized in youth welfare institutions. The two primary endpoints were the change in number of CD/ODD symptoms between (1) baseline (T1) and post-treatment (T3), and (2) between T1 and 12-week follow-up (T4). Results Both treatment groups showed reduced CD/ODD symptoms at T3 compared with T1 (95% CI: START NOW = −4.87, −2.49; TAU = −4.94, −2.30). There was no significant mean difference in CD/ODD symptom reduction from T1 to T3 between START NOW and TAU (−0.056; 95% CI = −1.860, 1.749; Hedge's g = −0.011). However, the START NOW group showed greater mean symptom reduction from T1 to T4 (−2.326; 95% CI = −4.274, −0.378; Hedge's g = −0.563). Additionally, secondary endpoint results revealed a reduction in staff reported aggression and parent-reported irritability at post assessment. Conclusions Although START NOW did not result in greater symptom reduction from baseline to post-treatment compared with TAU, the START NOW group showed greater symptom reduction from baseline to follow-up with a medium effect size, which indicates a clinically meaningful delayed treatment effect.